Cooperative mechanism of generalized stochastic resonance in a time-delayed fractional oscillator with random fluctuations on both mass and damping. (June 2020) - You, Pinlong; Lin, Lifeng; Wang, Huiqi
Highlights: A time-delayed FO with random fluctuations on both mass and damping is extended. System steady response is analyzed to reveal the cooperative mechanism of GSR behaviors. The non-monotonous phenomena of stochastic multi-resonance and inhibition are observed. The results provide extensive support for manipulating GSR behaviors from more dimensions. Abstract: In this paper, we investigate the generalized stochastic resonance (GSR) of a time-delayed fractional oscillator (FO) with the random dichotomous fluctuations on both mass and damping. By applying generalized fractional Shapiro–Loginov formula and Laplace transform, we analyze the system steady response and acquire the exact expression of output amplitude. Based on the evolutions of output amplitude varying with fractional order, time delay and dichotomous parameters, we reveal the cooperative mechanism to conduct a rich variety of GSR behaviors existing in this system. Particularly, it is found that time delay has little effect on the diversities of GSR, but plays an important role in amplifying the output amplitude. These results will provide more extensive support for manipulating resonant behaviors through system parameter control in the potential applications.